A Possible Ambivalence in Plato’s Approach to Mimesis and Poetry - MAJERI, Liana (Studia Universitatis Babeș-Bolyai Philosophia, 2025)
This paper explores the complexity of Plato’s approach to mimesis and poetry, focusing on his critique in Republic Books II, III, and X. While Plato dismisses poetry as ethically and epistemologically flawed, his arguments reveal a deeper tension between philosophy and artistic representation. Through an analysis of Plato’s tripartite division of reality, the critique of imitation, and the ethical concerns surrounding poetry’s influence, the paper examines whether his rejection of art is absolute or if it leaves room for an alternative poetic function. Drawing on Stephen Halliwell’s interpretation, the study highlights how Plato’s stance is shaped by a broader philosophical concern with truth, knowledge, and the role of art in society. The analysis considers whether Plato’s discussion of mimesis is not merely an attack on art but part of a larger philosophical negotiation over the intersection of aesthetics, morality, and epistemology.